2023
DOI: 10.1038/s41598-023-41553-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and associated factors among adult hypertensive patients in Referral Hospitals, Amhara Regional State

Yibeltal Yismaw Gela,
Daniel Gashaneh Belay,
Dagmawi Chilot
et al.

Abstract: Anemia is a risk factor for adverse cardiovascular disease outcomes in hypertensive patients. Chronic anemia increases preload, reduces afterload, and leads to increased cardiac output in hypertension patients. In the long term, this may result in maladaptive left ventricular hypertrophy, which in turn is a well-recognized risk factor for cardiovascular disease outcomes and all-cause mortality in hypertension. Low hemoglobin and hematocrit levels might be strongly indicate hypertensive end-organ damage, specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Besides, cigarette smoking affects the incidence of anemia as well as haematopoiesis [ 28 ] and poor physical activity was linked to increased risk of anemia [ 29 ]. In addition, participants’ health conditions, such as diabetes [ 29 ] and high blood pressure [ 30 ], were closely related to anemia. Similarly, in our study, significant statistical differences were found between anemia and normal groups in all the above potential variables.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, cigarette smoking affects the incidence of anemia as well as haematopoiesis [ 28 ] and poor physical activity was linked to increased risk of anemia [ 29 ]. In addition, participants’ health conditions, such as diabetes [ 29 ] and high blood pressure [ 30 ], were closely related to anemia. Similarly, in our study, significant statistical differences were found between anemia and normal groups in all the above potential variables.…”
Section: Discussionmentioning
confidence: 99%